PELATIHAN MENULIS TEKS PROSEDUR (PROCEDURE TEXT) BAGI SISWA KELAS X JURUSAN TEKNIK KENDARAAN RINGAN DAN OTOMOTIF SMK SWASTA YAPIM BIRU-BIRU - Bambang Nur Alamsyah Lubis; Fachri Yunanda; Azizah Husda; Nurmahyuni Asrul (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
Procedure text writing training at tenth grades students Teknik Kendaraan Ringan dan otomotif programs SMK SwastaYapim Biru-Biru was a training that aimed to maximize students' ability to write an English text, specifically procedure text and to make it easy in developing generic structures, linguistics feature of procedure text and type of procedure texts, and also students were able to answer questions related to the text. The subjects of the training were tenth grades students SMK Swasta Yapim Biru-Biru, Teknik Kendaraan Ringan dan Otomotif program. The communicative method was used as a method of training, presenting procedure text material which would become the basic knowledge and a benchmark successful of training that was given to students. There were several supporting instruments that were used to achieve successful of the training, such as laptops, cameras, projectors and printed texts, which were an important part of the training implementation. The results of training in writing procedure texts informed that students' ability in writing procedure texts, especially writing procedure texts in English had improved. It could be known based on successful of students in writing a procedure text that was be adapted to students program, Teknik Kendaraan Ringan dan Otomotif program.